Humidified Warmed CO2 Treatment Therapy Strategies Can Save Lives With Mitigation and Suppression of SARS-CoV-2 Infection: An Evidence Review - El-Betany, Alaa M. M.; Behiry, Enas M.; Gumbleton, Mark; Harding, Keith G. (Frontiers in Medicine, 2020)
The coronavirus disease (COVID-19) outbreak has presented enormous challenges for healthcare, societal and economic systems worldwide. There is an urgent global need for a universal vaccine to cover all SARS-CoV-2 mutant strains to stop the current COVID-19 pandemic and the threat of an inevitable second wave of coronavirus. Carbon dioxide is safe and superior antimicrobial, which suggests it should be effective against coronaviruses and mutants thereof. Depending on the therapeutic regime, CO2 could also ameliorate other COVID-19 symptoms as it has also been reported to have antioxidant, anti-inflammation, anti-cytokine effects and to stimulate the human immune system. Moreover, CO2 has beneficial effects on respiratory physiology, cardiovascular health, and human nervous systems. This article reviews the rationale of early treatment by inhaling safe doses of warmed humidified CO2 gas, either alone or as a carrier gas to deliver other inhaled drugs may help save lives by suppressing SARS-CoV-2 infections and excessive inflammatory responses. We suggest testing this somewhat counter-intuitive, but low tech and safe intervention for its suitability as a preventive measure and treatment against COVID-19. Overall, development and evaluation of this therapy now may provide a safe and economical tool for use not only during the current pandemic but also for any future outbreaks of respiratory diseases and related conditions.